Using Microwave Irradiation for synthesis of Imides consist of Pyromellitimide - Saedi, Habib (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Bispyromellitimides are an important class of substrates in polymer chemistry as monomers in polyimides or their copolymers synthesis.A fast and efficient microwave-assisted synthetic procedure for the preparation of series of these compounds 3(a-h) from the reaction of pyromellitic anhydride and aniline or its derivatives (a-h) is described. Elemental analysis, FT-IR and1H-FT-NMR Spectra revealed the confirmation of these compounds in good agreement.